2017
DOI: 10.1080/09593330.2017.1344732
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cr(VI) on nano Uio-66-NH2MOFs in water

Abstract: An efficient adsorbent, nano Uio-66-NH Metal-organic frameworks (MOFs), for the high efficiency removal of Cr(VI) from aqueous solution was successfully synthesized. The adsorbent was characterized and its performance in Cr(VI) removal was evaluated for the first time. Kinetic data reveal that the Cr(VI) adsorption is rapid in the beginning followed by a slower adsorption process; The Cr(VI) adsorption kinetics were well described by the pseudo-second-order kinetics model. The calculated adsorption capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…However, the new absorption peaks for the vibration of aromatic ring of MB at 890 cm −1 and 1600 cm −1 could be clearly observed [52], which showed that the MB was immobilized on surface of ZIF-8-loaded UiO-66-NH 2 . The peaks at 1571 cm −1 (C=O), 1257 cm −1 (C–N), and 426 cm −1 (Zn–N) of ZIF-8-loaded UiO-66-NH 2 shifted and showed a significant decrease in intensity after MB adsorption [28,53,54]. This could be explained by the following assumptions: (i) MB, a cationic dye, is more inclined to be absorbed on negatively charged surfaces by electrostatic interaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the new absorption peaks for the vibration of aromatic ring of MB at 890 cm −1 and 1600 cm −1 could be clearly observed [52], which showed that the MB was immobilized on surface of ZIF-8-loaded UiO-66-NH 2 . The peaks at 1571 cm −1 (C=O), 1257 cm −1 (C–N), and 426 cm −1 (Zn–N) of ZIF-8-loaded UiO-66-NH 2 shifted and showed a significant decrease in intensity after MB adsorption [28,53,54]. This could be explained by the following assumptions: (i) MB, a cationic dye, is more inclined to be absorbed on negatively charged surfaces by electrostatic interaction.…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by the positively charged character of UiO-66-NH 2 -PC nanoparticles due to the existence of amino groups and zirconium ions in the framework structures. 31,32 3.2.6 Surface roughness of TFC and TFN membranes. The surface roughness of TFC and TFN membranes was studied by AFM measurement.…”
Section: Characterization Of Uio-66-nh 2 and Uio-66-nh 2 -Pcmentioning
confidence: 99%
“…The bifunctionality of the UiO-66 materials has been achieved through:i )the linker defects generation,w hich are known to be efficient adsorption positions for Cr VI ;i i) the electron-donor groups incorporation (i.e.,-(OH) 2 ,-NH 2 )a tt he organic linkers, which work as active functionalitiest hat can directly trigger the Cr VI to Cr III reduction,a nd finally,i ii)the combination of the adsorption and posterior photo-reduction of Cr VI to Cr III for the specific case of photoactive UiO-66-NH 2 material. [57][58][59] After operation, chromium speciation has been fully determined by means of UV/Vis and EPR spectroscopy,q uantifying the Cr VI to Cr III reduction efficiency fore ach material. For comparison purpose, adsorptiona nd posterior speciation analysis have been also studied for trivalent chromium species, in order to understand the possible chromium immobilization mechanismsi na hypothetical case of full Cr VI to Cr III transformation.…”
Section: Introductionmentioning
confidence: 99%